(untitled) (Journal of Parents and Teachers, 2018)
In the present article a general presentation of the method of Open Calculation Based on Numbers (ABN) is made, highlighting its main features and the differential points with respect to other mathematical methods and also with respect to the traditional calculation. Another important point is the approach by the method of problem solving, as well as the specific preparation of students for learning maths on secondary school.